Pengaruh Kecerdasan Emosional dan Teknologi Informasi terhadap Kinerja yang Dimediasi oleh Motivasi pada Pengajar PNS Sekolah Tinggi Multi Media MMTC Yogyakarta - Kahandi Putra, Audi; Subyantoro, Arief; Heru Kristanto, R. (CV. Strata Persada Academia, 2024)
This research aims to analyze the impact of emotional intelligence and information technology on performance, which is mediated by motivation in civil servant teachers at the Sekolah Tinggi Multi Media MMTC Yogyakarta. This quantitative research uses a saturated sampling technique with a total of 35 civil servant teachers at Sekolah Tinggi Multi Media MMTC Yogyakarta as respondents. Research data was obtained through the direct distribution of questionnaires. Research data was tested statistically via Smart PLS with P-Value Criteria ≤ 0.05. The research results show that emotional intelligence and information technology positively affect the performance of civil servants at the Sekolah Tinggi Multi Media MMTC Yogyakarta. Mediation proves that motivation can mediate the relationship between emotional intelligence and information technology and performance.